2020
DOI: 10.3791/61267
|View full text |Cite|
|
Sign up to set email alerts
|

Involving Individuals with Developmental Language Disorder and their Parents/Carers in Research Priority Setting

Abstract: A protocol for involving individuals presenting with developmental language disorder (DLD) (iDLD) and their parents/carers (iDLDPC) in a research priority setting exercise is presented. iDLD have difficulties with communication skills, such as understanding language, word-finding and discourse. Such difficulties mean existing research priority setting protocols are difficult for iDLD to access, since they require sophisticated communication skills. Thus, a novel protocol for involving iDLD in these exercises i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“… 52 Alternatively, a modified ranking activity and data integration method to increase accessibility of the exercise to patients and the public could be implemented. 39 Following a recent evaluation of the overall project by the steering group, many of these and other ideas will be incorporated into future RCSLT PSPs. For example, training SLTs in identifying and supporting patients on their caseloads to participate at every stage of the priority-setting, from design to dissemination.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“… 52 Alternatively, a modified ranking activity and data integration method to increase accessibility of the exercise to patients and the public could be implemented. 39 Following a recent evaluation of the overall project by the steering group, many of these and other ideas will be incorporated into future RCSLT PSPs. For example, training SLTs in identifying and supporting patients on their caseloads to participate at every stage of the priority-setting, from design to dissemination.…”
Section: Discussionmentioning
confidence: 99%
“…This, along with ensuring a greater representation of patients/carers, should be considered when planning future PSPs 52. Alternatively, a modified ranking activity and data integration method to increase accessibility of the exercise to patients and the public could be implemented 39. Following a recent evaluation of the overall project by the steering group, many of these and other ideas will be incorporated into future RCSLT PSPs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The authors identified a broad range of aphasia‐related issues including treatment effectiveness, therapy timing and intensity, assessment and management of depression in people with aphasia, the impact of trained volunteers and carers on communication, and the effects of communication aids (Franklin et al 2018). Currently, in the UK, the RCSLT is undertaking a prioritization study with children with developmental language delay, their parents/carers and specialist SLTs (Chadd and Kulkarni 2020).…”
Section: Introductionmentioning
confidence: 99%